Antigenic stimulation regulates the level of expression of interleukin 2 receptor on human T cells. - Hemler, M E (1984)
Antigen-specific, interleukin 2 (IL-2)-dependent human T-cell lines and clones were utilized to study the relationship between IL-2 receptor expression and antigenic stimulation. T cells that had not been exposed to antigen for 2 wk or more expressed a stable low level of the IL-2 receptor. After reexposure to antigen, a 10- to 30-fold increase in the level of the IL-2 receptor was rapidly induced, with the peak level of IL-2 receptor expression occurring at 15-30 hr. This peak preceded the peak in cell proliferation [( 3H]thymidine incorporation), which was at 48-72 hr. Within 2-14 days after peak IL-2 receptor expression, it returned to a low base-line level. The transient elevation in IL-2 receptor level was antigen specific because it occurred in response to specific allogeneic stimulator cells but not after exposure to cells expressing irrelevant HLA allotypes. The levels of other cell-surface proteins, including those related to T-cell activation (HLA-DR, T10, 4F2, A-1A5) as well as T3, which has been proposed to be a component of the T-cell receptor complex for antigen, did not change in response to antigen exposure or deprivation. Because IL-2 was maintained at a consistently high level throughout these experiments, the antigen-induced changes in the IL-2 receptor appear to be independent of changes induced by IL-2 itself. Both cloned T cells and mixed populations containing T4 and T8 subsets showed similar IL-2 receptor responsiveness, indicating that this finding is generalizable to most, if not to all, antigen-responsive T cells.